2014
DOI: 10.1080/15389588.2014.936407
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Billboards on Driver Visual Behavior: A Systematic Literature Review

Abstract: Objective External distraction appears to affect at least 6–9% of distraction-affected motor vehicle collisions. Billboards may be good models for studying external distraction in general, and it is also desirable to understand billboard-related distraction per se. However, there has not yet been a clear consensus on the scope of billboard-related distraction or its dynamics with respect to characteristics of drivers, billboards, traffic, and the roadway. To narrow these knowledge gaps, a systematic literature… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
27
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 60 publications
(31 citation statements)
references
References 11 publications
3
27
1
Order By: Relevance
“…The literature review conducted by Decker et al (2015) concluded that the risk associated with billboards in most driving situations is likely minimal, but that this risk can vary widely with billboard characteristics, and possibly with driver, road, and traffic characteristics. Thus, the review suggested that future research in the field focus on identifying the specific qualities of drivers, billboards, and roadway/traffic environments that correspond to the highest risk of billboard-related distraction, and quantifying such distraction in these highest-risk situations and populations (i.e., as opposed to in the average, relatively low-risk case).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The literature review conducted by Decker et al (2015) concluded that the risk associated with billboards in most driving situations is likely minimal, but that this risk can vary widely with billboard characteristics, and possibly with driver, road, and traffic characteristics. Thus, the review suggested that future research in the field focus on identifying the specific qualities of drivers, billboards, and roadway/traffic environments that correspond to the highest risk of billboard-related distraction, and quantifying such distraction in these highest-risk situations and populations (i.e., as opposed to in the average, relatively low-risk case).…”
Section: Discussionmentioning
confidence: 99%
“…Glance types were stratified by length of glance (≥ 0.75 seconds and ≥ 2.0 seconds) to be consistent with previous work (Decker et al, 2015). 0.75 seconds has been suggested as the minimum perception-reaction time (PRT) for a vehicle slowing ahead of the driver (Smiley et al, 2004), and long glances of 2.0 seconds or longer have been shown in naturalistic studies to be especially associated with MVCs and other traffic incidents (Klauer, Dingus, Neale, Sudweeks, & Ramsey, 2006);…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations